Proposal of guidelines for the development of evaluation instruments for educational software - Godoi, Katia Alexandra de; Padovani, Stephania (InfoDesign, 2010)
In this study, we proposed guidelines for the development of evaluation instruments for educational software, based on the results of an analytical study of twenty three evaluation instruments, of a survey conducted with teachers and of two focus groups. Firstly, evaluation instruments for educational software are described and the need for user-centred instruments is addressed. Then, we present the research method, and propose guidelines for the development of evaluation instruments aimed at educational software. [ Download ]